(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The teaching strategy is represented as homogeneous steps, and the teacher can transform them into methods and teaching skills that suit the nature of the learner, the course, and the conditions of the educational situation to achieve a goal or objectives. The strategy (Yuadi) is teaching artistic concepts, which are manifested in the constructive composition of the artwork for the purpose of reaching its reflections in educating the aesthetic response of Students of the Department of Art Education, therefore, this problem is based on raising the following question:What is the extent of the reflection of the (Yoadi) strategy in teaching the artistic concepts of constructive composition of the artistic work on the education of the aesthetic response of the students of the Department of Art Education?As the current research aims to identify the teaching of artistic concepts according to the strategy (Yuadi) and its reflection on the aesthetic response of the students of the Department of Art Education, and to achieve the goal of the research, the researcher put the two zero hypotheses:null hypothesis (1):"There are no statistically significant differences at the level (0.05) between the mean scores of the students of the two groups (T, Z) in the aesthetic response post-test."null hypothesis (2):There are no statistically significant differences at the level (0.05) between the mean scores of the students of the two groups (T, Z) in their answers to the aesthetic response test to measure the effect of teaching with a secondary strategy.The research community consists of third grade students / Department of Art Education - College of Fine Arts / Baghdad who are studying art history for the academic year 2020-2021, and their number is (153) students distributed into (8) classes. To produce the results, the researcher used a set of statistical methods. Based on that, the research came out with the most important conclusions:1- The teaching process, according to Yawadi’s strategy, formed a positive aspect that was reflected in the development of the aesthetic response of art education students, as it provided them with educational experiences of artistic concepts, as the constructive composition of the artwork depends on it.2- The Yawadi strategy has contributed to raising the students’ motivation and their attention to the artistic concepts they were exposed to, which motivated them to answer the aesthetic response test.Keywords: Structural Composition - Yawadi’s Strategy - Artistic Concepts - Aesthetic Response.